HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA DENGAN TINGKAT KEMANDIRIAN ANAK KELAS 1 SD - Rahmawati, Ima; Dwi Fatmawati, Yeni (JURNAL KEPERAWATAN BINA SEHAT, 2010)
Self supporting is kind of or condition that self containedwithout depend on another person. Based of development task of scool child, a child is self-supporting if they have had the abilitty how to help themselves (self-help). To achieve the self supporting, child must optimize, self supporting that make possible to them to do everytything for themselves. Doing the development task and child self supporting needs parents guidance. While doing guidence needed good erudition so that parents can threat child correctly. The aims of this research is analyzing connection of parent’s erudition level with First grade of elementery school.The design’s research uses correlation with approach cross sectional. Parents populatin and First grade of elementary school sample technique uses techniqueprobability sampling type random sampling. Instrument that used questioner and observation sheet. Analysis Data uses Spearman Rho test. Analysis Data result shows level significant r = 0,000 < 0.05. Coefficient correlation 0,683 that mean found strong connectionbetween parents erudition level with child self supporting level.To be a self-supporting a child want to chance, family support and with environment surrounding them. In the family, parents have role to impersonates guide, and the aim of self-supporting child. Parents role is the most influence in the Development of child self supporting, and parents ,ust do coorperation with the teacher to give suitable punishment that is done by the child.Keyword: erudition, self supporting, parents, child.